Revolutions. Paraguay : the revolution was in the ballot box - Santos, Valéria; Claude, Philippe (Filmmaker); Solferino Images (Firm) (Wheeling, IL : Film Ideas, Inc., 2012)
On April 20th, 2008, carried by a tremendous popular support worthy of the greatest South American revolutions, Fernando Lugo, the "suspended" bishop, is elected president of the Republic of Paraguay. After sixty years of absolute power, the Colorado party is compelled to accept the changeover of political power. This documentary will enable us to discover the scarcely known country nestled deep into the heart of the South American continent, its unique social structure, its painful past and its surprising identity. By listening to the newly elected president, to his deposed Colorado opponents, to the specialists of the history of the country and to the people itself, they will help us understand why the Paraguayans, after so many years of dictatorship and unopposed governing, have entrusted their destiny to a free man: a religious figure who threw himself into the political arena to try and rescue his country of crime, injustice and poverty and to restore democracy.
Title from resource description page (viewed April 04, 2018).
In English.
Keywords: Lugo Méndez, Fernando, -- 1951-; Lugo Méndez, Fernando, -- 1951-; Presidents -- Paraguay; Democracy -- Paraguay; Elections -- Paraguay; Paraguay -- Politics and government -- 1989-; Présidents -- Paraguay; Élections -- Paraguay; Paraguay -- Politique et gouvernement -- 1989-; Democracy; Elections; Politics and government; Presidents; Paraguay; Since 1989; Documentary films; Feature films; Nonfiction films; Documentary films; Nonfiction films; Feature films; Documentaires; Films autres que de fiction